1998
DOI: 10.1038/sj.onc.1201620
|View full text |Cite
|
Sign up to set email alerts
|

Tumour specific regulation of telomerase RNA gene expression visualized by in situ hybridization

Abstract: Maintenance of telomere structure by the ribonucleoprotein enzyme telomerase is considered central to the development of most human cancers. However, regulatory mechanisms governing telomerase expression during oncogenesis are largely unknown. We address potential tumour-speci®c regulation of telomerase RNA gene expression by RNA in situ hybridization to over 300 tumour samples of germ cell and epithelial origin. Twenty-six per cent of non-small cell lung cancers (NSCLC), expressed detectable levels of the tel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(42 citation statements)
references
References 16 publications
3
39
0
Order By: Relevance
“…In addition, we have recently shown tumourspeci®c patterns of hTR gene expression with clear di erentials in expression between cancerous and adjacent normal tissue (Soder et al, 1997a,b). Therefore, the hTR gene promoter may be of considerable use in genetic therapies requiring selective expression of therapeutic genes in cancer cells expressing high levels of hTR (Connors, 1995;Miller and Whelan, 1997;Soder et al, 1997a). The constructs described in the present study will be ideal for more focused gene therapy studies and the development of transcription based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In addition, we have recently shown tumourspeci®c patterns of hTR gene expression with clear di erentials in expression between cancerous and adjacent normal tissue (Soder et al, 1997a,b). Therefore, the hTR gene promoter may be of considerable use in genetic therapies requiring selective expression of therapeutic genes in cancer cells expressing high levels of hTR (Connors, 1995;Miller and Whelan, 1997;Soder et al, 1997a). The constructs described in the present study will be ideal for more focused gene therapy studies and the development of transcription based therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of telomerase RNA gene expression vary during normal development and between normal and cancerous cells and tissues (Avilion et al, 1996;Bestilny et al, 1996;Blasco et al, 1995Blasco et al, , 1996Bodnar et al, 1996;Broccoli et al, 1996;Feng et al, 1995;Kuniyasu et al, 1997;Soder et al, 1997a). Knowledge of telomerase RNA gene expression should therefore aid our understanding of the signal transduction pathways linking telomere attrition to proliferation, cellular senescence, di erentiation and oncogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…11 Additional studies have shown it to be upregulated in solid tumours. 12,13 To determine if hTR levels may be limiting for telomere maintenance in CP CML, we performed Q-RT-PCR for hTR in CML vs normal CD34 þ selected cells (Figure 7). Interestingly, the mean hTR level in CML CD34 þ cells was some five-fold lower than that for normal.…”
Section: Accumulation Of Full-length Htert Transcripts In Cd34 þ Cellmentioning
confidence: 99%